Materials Characteristic of the Bronze and Iron Periods, discovered by R. Torosyan from Excavations of Early Agricultural Sites in the Ararat Valley - Tadevosyan, Anzhela (History and Culture, 2025)
Armenian archaeologist Rafik Torosyan is known to the scientific community mainly for his works devoted to the formation and development of the Early Agricultural society in Armenia. In fact, the sphere of his scientific interests was much wider, covering practically all periods available for archeological research. R. Rorosyan’s excavations of Early Agricultural settlements of the Ararat Valley in 1960-1970. allowed to interpret the most ancient culture of the region in a new view, to reveal the peculiarities and characteristic features of the Neolithic - Chalcolithic culture. At the same time, materials from the upper horizons, characteristic of the Bronze and Iron periods (with the exception of materials from burials in the territory of the open biofilter of Echmiadzin) are rarely mentioned in the scientific literature. Although materials from the Early Bronze Age are scarce, their wide representation suggests a fairly dense settlement of this territory. During this period, the study area was in the sphere of attraction of Mohrablur. Materials characteristic of the Middle Bronze Age are presented both in burials and settlements. Funerary monuments are characteristic of the entire Middle Bronze Age, while the territory of settlements is re-populated starting from the beginning of the 2-nd millennium BC. and are characterized by painted ceramics. The development of the territory continues in the Late Bronze and Early Iron periods, when this territory was part of the Metsamor agglomeration.